CD8highCD57+ T-cell population as an independent predictor of response to chemoradiation therapy in extensive-stage small cell lung cancer. Issue 2 (November 2015) - Dobrovolskienė, Neringa T.; Cicėnas, Saulius; Kazlauskaitė, Nijolė; Mišeikytė-Kaubrienė, Edita; Krasko, Jan A.; Ostapenko, Valerijus; Pašukonienė, Vita; Strioga, Marius M.
Highlights: We analysed peripheral blood immune parameters in extensive-stage SCLC patients. Patients received either chemotherapy alone, or chemoradiotherapy or best supportive care. We identified an immune profile, predictive of response to chemoradiotherapy. Only chemoradiotherapy was beneficial in patients with a favourable immune profile. Abstract: Objectives: Tangible clinical benefit is achieved in only a relatively small proportion of extensive-stage small cell lung cancer (SCLC) patients receiving current treatment strategies. Therefore, a more personalized use of current and novel treatment approaches is of critical importance. Individualized therapy relies on the identification of specific biomarkers predictive of response to a particular type of cancer treatment. Immune-related parameters emerge as powerful biomarkers among a variety of predictors of clinical response to various types of cancer treatment. Patients and methods: Using multicolor flow cytometry, we evaluated a predictive value of CD8 high CD57 + T-cell population and its immunosuppressive (FOXP3 +, NKG2A + ) and cytotoxic (Perforin + ) subsets in the peripheral blood of extensive-stage SCLC patients ( n = 82) treated with either chemotherapy-alone ( n = 24), or chemoradiation therapy ( n = 42), or receiving best supportive care ( n = 16). Results: The low level (<20%) of CD8 high CD57 + T cells within the peripheral blood CD8 + T-cell population and the low level (<3%) of the immunosuppressive FOXP3-positive subset within the CD8 high CD57 + T-cell population were independent predictors of a better response to treatment with chemoradiation therapy, but not with chemotherapy alone or best supportive care. Importantly there was no significant survival difference between SCLC patients who were: (i) treated with chemoradiation, but had an unfavourable immune profile (≥20% of CD8 high CD57 + T cells and ≥3% of its FOXP3-positive subset), (ii) treated with chemotherapy alone, or (iii) received best supportive care. Conclusions: We show that only a combination of chemotherapy with radiation therapy offered a considerable survival benefit that was confined to a subset of extensive-stage SCLC patients with a favourable predictive immune profile in the peripheral blood.